2021
DOI: 10.7554/elife.64618
|View full text |Cite
|
Sign up to set email alerts
|

Genomic epidemiology of COVID-19 in care homes in the east of England

Abstract: COVID-19 poses a major challenge to care homes, as SARS-CoV-2 is readily transmitted and causes disproportionately severe disease in older people. Here, 1,167 residents from 337 care homes were identified from a dataset of 6,600 COVID-19 cases from the East of England. Older age and being a care home resident were associated with increased mortality. SARS-CoV-2 genomes were available for 700 residents from 292 care homes. By integrating genomic and temporal data, 409 viral clusters within the 292 homes were id… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 42 publications
1
44
0
Order By: Relevance
“…Three studies defined a consistent method in their study to identify clusters. 18 , 19 , 27 These studies used Phylogenetic Assignment of Named Global Outbreak Lineages software or a more granular clustering algorithm in the COVID-19 Genomics UK (COG-UK) Consortium pipeline, 19 transcluster algorithm, 18 or single nucleotide polymorphism (SNP) distance. 27 One study provides a rationale for how clusters were identified without providing a defined criteria for selecting genomic clusters.…”
Section: Study Characteristics and Quality Of Outcome Measuresmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies defined a consistent method in their study to identify clusters. 18 , 19 , 27 These studies used Phylogenetic Assignment of Named Global Outbreak Lineages software or a more granular clustering algorithm in the COVID-19 Genomics UK (COG-UK) Consortium pipeline, 19 transcluster algorithm, 18 or single nucleotide polymorphism (SNP) distance. 27 One study provides a rationale for how clusters were identified without providing a defined criteria for selecting genomic clusters.…”
Section: Study Characteristics and Quality Of Outcome Measuresmentioning
confidence: 99%
“…Furthermore, assuming a mutation rate of approximately 2·5 SNPs per month 19 allows for the estimation of the amount of variation expected in a phylogeny at any particular timepoint in a series. Additionally, only two studies mention the use of negative controls 18 , 19 and no studies have released the sequencing reads found in the negative controls publicly. Many sample preparation protocols use amplification techniques that can also amplify contamination and give false results, particularly when the viral load in the source material is low.…”
Section: Study Characteristics and Quality Of Outcome Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…In the limited instances where viral genomic data were analysed, this information was used to confirm or complement a purely epidemiological approach. [6][7][8][9] Elucidating the source of transmission events on the basis of viral genetic relatedness alone also entails considerable uncertainty due to the slow evolutionary rate of SARS-CoV-2. [10] In the time scale of an outbreak, a large proportion of individuals are infected by viruses too genetically similar to each other to distinguish genuine transmission events from unrelated infections.…”
Section: Introductionmentioning
confidence: 99%